SIKAP HORMAT SANTRI TERHADAP GURU MENURUT KITAB ADAB KH. MUHAMMAD - admin, admin; Rubiyad, Adib (Prodi PAI IAILM Suryalaya, 2021)
This study aims to determine the concept of students' respect for teachers according to the book of adab KH. Muhammad. This study uses a qualitative approach, based on a literature review or literature study. The data collection method used in this study is the documentation method, which is a way of collecting data through written relics, such as archives and books on opinions, theories, arguments or laws. The Book of Adab written by KH. This Muhammad discusses character education for a student written using Arabic pegon in Javanese Kromo (Javanese limp). This study was attended by students. The discussions in the Book of Adab consist of twelve chapters, namely: Student etiquette towards teachers, children towards parents and the people towards the government, etiquette of people seeking knowledge, etiquette in making friends, manners of people who are knowledgeable towards themselves, etiquette for giving alms, etiquette for people who are invited, etiquette for eating, etiquette for eating when visiting, drinking etiquette, etiquette for respecting guests and manners for giving food to guests.